Implementasi Peraturan Daerah No. 10 Tahun 2012 tentang Retribusi Pelayanan Kebersihan dan Kontribusinya Dalam Peningkatan P.A.D Kota Medan - Ali Rahman (Jurnal Smart Hukum (JSH), 2022)
Optimizing PAD, the regional retribution sector is a very potential sector for the excavation and extension of its management because the regional retribution is levied on the remuneration provided by the local government. In addition, the implementation of the collection of regional levies is conducted beyond the time specified by law and regulation, as long as the local government can provide services to hold the collection. This study aims to determine the implementation of Local Regulation No. 10 of 2012 on the Retribution of Cleanliness Services and its contribution in increasing the Local Revenue of Medan City and the constraints in its implementation and to know the efforts made in overcoming the obstacles in the implementation of Local Regulation No. 10 Year 2012 About Retribution and its contribution to the increase of Medan District Revenue. This research uses descriptive method through normative approach (legal research) to obtain secondary data. The data collected will be carefully analyzed using qualitative analysis or elaborated with sentences. Result of research indicate that levy of cleanliness in Medan City is one of source of Original Revenue. Implementation of city cleanliness levy policy of Medan is based on Local Regulation No. 10 Year 2012 About Retribution of Cleaning Service. The implementation is carried out in a coordinated manner between the Sanitation Department and the Regional Tax and Retribution Management Agency while the cleaning service is the responsibility of the Sanitation Department. Implementation of this policy has not been maximized, the policy socialization process has not run well, the potential excavation is still not done the target acceptance and the realization is still low. The contribution of cleanliness levy to PAD is still lacking, whereas based on the existing potential, the contribution of cleanliness to PAD can still be improved. So it is necessary to supervise the collection of cleaning retributions because in 2020 the results of the retribution received by the regional treasury amounted to Rp. Rp.246.044.000,00 but only reached Rp.143.705.500.00 which is around 58.41%